Caracterização molecular de estafilococos isolados de vacas com mastite subclínica e ordenhadores - Fontana, V. L. D. S.; Mendes-Giannini, Maria José Soares [UNESP]; Fontana, C. A. P.; Leite, Clarice Queico Fujimura [UNESP]; Stella, A. E. (Instituto Biológico, 2012)
As bactérias isoladas para o estudo foram oriundas de 96 vacas (163 tetos positivos no California Mastitis Test - CMT e nove suabes de mão de ordenhadores, de nove propriedades rurais situadas no Município de Jataí, GO. Das amostras coletadas (163 de leite e 9 de suabes de mão), foram identificadas 83 linhagens do gênero Staphylococcus spp., sendo S. aureus (31), S. saprophyticus (29), S. xylosus (17), S. epidermidis (4) e S. intermedius (2). No presente estudo, 35 perfis foram gerados de 83 amostras de Staphylococcus e o perfil IA (64,5%) de S. aureus, IS (44,8%) de S. saprophyticus, VX (35,3%) de S. xylosus e IIE (50%) de S. epidermidis foram os mais prevalentes. Houve predominância de um tipo entre os isolados de S. aureus nos rebanhos. Cepas idênticas foram encontradas em diferentes animais de uma mesma propriedade, assim como houve identidade genética entre cepa oriunda da mão do ordenhador e do animal. Assim, nossos dados mostraram que há variabilidade entre os isolados, mas também similaridade genética de algumas cepas concentradas em determinados locais. A similaridade genética pode compreender um complexo de clones relacionados, sugerindo relação de contaminação e transferência cruzada entre as cepas de origem humana e animal.

Bacteria isolated for this study were derived from 96c ows (163 quarters positive for the California Mastitis Test (CMT) and 9 swabs taken from the hands of milking staff, on 9 farms in the municipality of Jataí, state of Goiás, Brazil. of the samples collected (163 from milk and 9 swabs taken from hands) 83 strains of the genus Staphylococcus spp. were identified: S. aureus (31), S. saprophyticus (29), S. xylosus (17), S. epidermidis (4), S. intermedius (2).In this study,35 profiles were generated from 83 samples of Staphylococcus, and profile IA (64.5%) of S. aureus, IS (44.8%) of S. Saprophyticus, VX (35.3%) of S. xylosus and IIE (50%) of S. epidermidis were the most prevalent. There was a predominance of one type among isolates of S. aureus in herds. Identical strains were found in different animals of the same farm, as well as genetic identity between the strain isolated from the hand of the milker and the animal. Thus, our data showed that there is variability among isolates, but also genetic similarity of some strains concentrated in certain locations. The genetic similarity may comprise a complex of related clones, suggesting a relationship of cross-contamination and transfer among strains of human and animal origin.
Molecular characterization of staphylococci isolated from bovine mastitis and milking workers
Keywords: Mastite bovina subclínica; Staphylococcus; RAPD-PCR; Subclinical bovine mastitis; Staphylococcus spp.; RAPD-PCR